2022
DOI: 10.1073/pnas.2110428119
|View full text |Cite
|
Sign up to set email alerts
|

LCDR regulates the integrity of lysosomal membrane by hnRNP K–stabilized LAPTM5 transcript and promotes cell survival

Abstract: Lysosome plays important roles in cellular homeostasis, and its dysregulation contributes to tumor growth and survival. However, the understanding of regulation and the underlying mechanism of lysosome in cancer survival is incomplete. Here, we reveal a role for a histone acetylation–regulated long noncoding RNA termed lysosome cell death regulator (LCDR) in lung cancer cell survival, in which its knockdown promotes apoptosis. Mechanistically, LCDR binds to heterogenous nuclear ribonucleoprotein K (hnRNP K) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Although all of these results are consistent with the data by KD of LCDR or hnRNPK expression to reduce LAPTM5 expression in NCI-H1299 cells, the observed LAPTM5 function in the regulation of the programmed cell death that was unrelated to other apoptosis-causing genes in Yang et al. ( 6 ) is interesting. But the data appear to contradict studies where overexpression of LAPTM5 in neuroblastoma cells was found to cause LMP and nonapoptotic cell death ( 12 ) and in HeLa cells to induce cleavage of Mcl-1, Bid, caspases, and PARP, leading to mitochondria-dependent apoptosis ( 13 ).…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Although all of these results are consistent with the data by KD of LCDR or hnRNPK expression to reduce LAPTM5 expression in NCI-H1299 cells, the observed LAPTM5 function in the regulation of the programmed cell death that was unrelated to other apoptosis-causing genes in Yang et al. ( 6 ) is interesting. But the data appear to contradict studies where overexpression of LAPTM5 in neuroblastoma cells was found to cause LMP and nonapoptotic cell death ( 12 ) and in HeLa cells to induce cleavage of Mcl-1, Bid, caspases, and PARP, leading to mitochondria-dependent apoptosis ( 13 ).…”
supporting
confidence: 87%
“…In PNAS, Yang et al. ( 6 ) explore the expression profile of cellular lncRNAs in the presence of the histone deacetylase inhibitor Trichostatin A and identify a ∼2-kb-long nuclear lncRNA, ENSG00000273148 or LINC00653, highly expressed from chr20 in p53-null, non–small-cell lung cancer cell line NCI-H1299 cells. Yang et al.…”
mentioning
confidence: 99%
See 3 more Smart Citations